An Analisis Laporan Arus Kas sebagai Dasar Pengukuran Kinerja Keuangan Rumah Sakit Umum Daerah (studi kasus pada RSUD di Sumatera Selatan) - Rika Henda Safitri (Jurnal Akuntansi, 2017)
The purpose of this research it is analyzing the ratio of cash flow in managing funds rsud in south and to analyze how the financial performance of the hospital in south sumatra based on the analysis of the ratio of cash flow . The methodology that was used in writing this is desksriptif quantitative analysis by the use of the ratio of cash flow. Data in research is secondary data of the annual financial report which includes the hospital , cash flow report , and the primary data which includes information through the internet and journal. The results of research that it is processed using the ratio of cash flow this indicates that the performance of the district general hospital in south is not good. This is shown by the results of the analysis the ratio of cash flow on average less than 1. An analysis of the ratio of cash flow performance measurement method is not used .Because the ratio of cash flow analysis using data and a lot of equity , while in the district general hospital , not showing the data.